The Influence of Total Physical Response (TPR) Method in Mastering Arabic Vocabulary - Nimas Aulia; Rohmatun Lukluk Isnaini; Agung Setiyawan (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2023)
The lack of mastery in students' vocabulary greatly influences the objectives of learning Arabic, as students lack interest in following Arabic lessons, which are considered boring. This study aims to determine the Arabic vocabulary mastery of fifth grade students at the elementary school (SD) using the total physical response (TPR) method. The type of research used is quantitative research with an experimental research process. Data collection techniques used in the form of observation, interviews, and tests The data obtained showed that this study used normality test techniques, hypothesis testing, and one-sample t tests on Arabic vocabulary mastery. The sample in this study was 23 students in class V, using the pretest and posttest. The results of this study showed significant results: mastery of Arabic vocabulary before treatment was carried out using the total physical response (TPR) method obtained an average value of 69.35 with a standard deviation of 9.208. While the students' mastery of Arabic vocabulary improved after the total physical response (TPR) method was applied, the average value was 80.87, with a standard deviation of 10.407. There was an increase in Arabic vocabulary mastery after the total physical response (TPR) method was applied. So it can be concluded that the Total Physical Response (TPR) method is influential and suitable for increasing fifth grade students' mastery of Arabic vocabulary. Abstrak Faktor kurangnya penguasaan kosakata Arab siswa adalah kurangnya minat siswa dalam mengikuti pelajaran bahasa Arab yang dianggap membosankan. Penelitian ini bertujuan untuk mengetahui penguasaan kosakata bahasa Arab siswa kelas V Sekolah Dasar dengan menggunakan metode Total Physical Response (TPR). Penelitian ini adalah penelitian kuantitatif dengan metode eksperimen. Teknik pengumpulan data yang digunakan berupa tes, observasi, dan wawancara. Data kuantitatif penelitian diperoleh berdasarkan pretest dan posttest yang diuji normalitas, uji hipotesis dan uji one-sample t test terhadap penguasaan kosakata bahasa Arab. Sampel penelitian adalah siswa kelas V berjumlah 23 siswa. Hasil penelitian ini menunjukkan bahwa penguasaan kosakata bahasa Arab sebelum dilakukan treatment menggunakan metode TPR diperoleh nilai rata-rata sebesar 69.35, dengan standar deviasi sebesar 9.208. Kemudian setelah diterapkan metode TPR nilai rata-rata siswa menjadi 80.87, dengan standar deviasi sebesar 10.407. Berdasarkan hasil tersebut terdapat peningkatan penguasaan kosakata bahasa Arab setelah diterapkanya metode TPR. Sehingga dapat disimpulkan bahwa metode TPR berpengaruh dan cocok digunakan untuk meningkatkan penguasaan kosakata bahasa Arab siswa SD.